Synthesis and cytostatic and antiviral activities of 2'-deoxy-2',2'-difluororibo- and 2'-deoxy-2'-fluororibonucleosides derived from 7-(Het)aryl-7-deazaadenines - Perlíková, Pavla; Eberlin, Ludovic; Ménová, Petra; Raindlová, Veronika; Slavětínská, Lenka; Tloušťová, Eva; Bahador, Gina; Lee, Yu-Jen; Hocek, Michal (ChemMedChem, 2013)
A series of sugar-modified derivatives of cytostatic 7-heteroaryl-7-deazaadenosines (2'-deoxy-2'-fluororibo- and 2'-deoxy-2',2'-difluororibonucleosides) bearing an aryl or heteroaryl group at position 7 was prepared and screened for biological activity. The difluororibonucleosides were prepared by non- stereoselective glycosidation of 6-chloro-7-deazapurine with benzoyl-protected 2-deoxy-2,2-difluoro-D-erythro-pentofuranosyl-1-mesylate, followed by amination and aqueous Suzuki cross-couplings with (het)arylboronic acids. The fluororibo derivatives were prepared by aqueous palladium-catalyzed cross-coupling reactions of the corresponding 7-iodo-7-deazaadenine 2'-deoxy-2'-fluororibonucleoside 20 with (het)arylboronic acids. The key intermediate 20 was prepared by a six-step sequence from the corresponding arabinonucleoside by selective protection of 3'- and 5'-hydroxy groups with acid-labile groups, followed by stereoselective SN 2 fluorination and deprotection. Some of the title nucleosides and 7-iodo-7-deazaadenine intermediates showed micromolar cytostatic or anti-HCV activity. The most active were 7-iodo and 7-ethynyl derivatives. The corresponding 2'-deoxy-2',2'-difluororibonucleoside 5'-O-triphosphates were found to be good substrates for bacterial DNA polymerases, but are inhibitors of human polymerase α.
Keywords: HL-60 buňky; buňky Hep G2; inhibitory syntézy nukleových kyselin; Antiviral Agents; ribonukleosidy; vztahy mezi strukturou a aktivitou; DNA-dependentní DNA-polymerasy; cytostatické látky; Cell Proliferation; Humans; Structure-Activity Relationship; DNA-Directed DNA Polymerase; Molecular Structure; nádorové buněčné linie; Antineoplastic Agents; HL-60 Cells; Cytostatic Agents; HeLa buňky; Adenine; Hepacivirus; Ribonucleosides; protinádorové látky; Nucleic Acid Synthesis Inhibitors; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Hep G2 Cells; Drug Screening Assays, Antitumor; screeningové testy protinádorových léčiv; proliferace buněk; Cell Survival; viabilita buněk; antivirové látky; adenin; Dose-Response Relationship, Drug; HeLa Cells; vztah mezi dávkou a účinkem léčiva; lidé; Cell Line, Tumor; molekulární struktura